Ideology, politics, and language policies : focus on English - Ricento, Thomas (Impact, studies in language and society, 2000)
This volume critically examines the effects of the spread of English from colonialism to the 'New World Order'. The research explores the complex and often contradictory roles English has played in national development. Historical analyses and case studies by leading researchers in language policy studies reveal that deterministic relationships between imperial languages, such as English, and societal hierarchies are untenable, and that support of vernacular languages in education and public life can serve diverse ideologies and political agendas. Areas and countries investigated include Europ.